Early intracardiac thrombus and pulmonary embolus after trauma - Desai, Neel; Heid, Julia; Leitch, Andrew R. (BMJ case reports, 2017)
Here, we present the case of a patient with the findings of an early intracardiac thrombus and a pulmonary embolus after major trauma. A large clot was identified extending from the inferior vena cava into the right atrium and ventricle in the setting of preserved right ventricular function. Post-traumatic intracardiac thrombus is extremely rare and no comparable cases have previously been described in the absence of a congenital heart defect and obvious myocardial injury. Best practice afterpost-traumatic intracardiac thrombus is not well established but we found that early inferior vena cava filter placement and treatment with therapeutic coagulation resulted in clinical improvement, resolution of the thrombus and no further emboli. The successful use of rivaroxaban, a direct-acting oral anticoagulant, to treat a right heart thrombus has, to our knowledge, not previously been reported. Early acute traumatic coagulopathy has received much attention but the hypercoagulable state that often follows is less well appreciated.